Layered 2D alkyldiammonium lead iodide perovskites: synthesis, characterization, and use in solar cells. Issue 40 (23rd September 2016) - Safdari, Majid; Svensson, Per H.; Hoang, Minh Tam; Oh, Ilwhan; Kloo, Lars; Gardner, James M.
Abstract : The synthetic route and properties of three 2D hybrid organic/inorganic lead iodide perovskite materials are reported. Abstract : The synthetic route and properties of three 2D hybrid organic/inorganic lead iodide perovskite materials are reported. The 2D perovskites were synthesized from the reaction between PbI2 and the di-cations of 1, 4-diaminobutane, 1, 6-diaminohexane, and 1, 8-diaminooctane. The resulting products were [NH3 (CH2 )4 NH3 ]PbI4 (BdAPbI4 ), [NH3 (CH2 )6 NH3 ]PbI4 (HdAPbI4 ), and [NH3 (CH2 )8 NH3 ]PbI4 (OdAPbI4 ). Structural characterization shows that two dimensional perovskite structures were formed with inorganic structural planes separated by organic layers. Absorption spectra show band gaps of 2.37 eV (BdAPbI4 ), 2.44 eV (HdAPbI4 ), and 2.55 eV (OdAPbI4 ). The 2D perovskite materials were investigated as light absorbing materials in solid state solar cells. The best performing material under moist, ambient conditions wasBdAPbI4 (1.08% efficiency), which was comparable to methylammonium Pb(ii ) iodide (MAPbI3 ) solar cells (2.1% efficiency) manufactured and studied under analogous conditions. When compared toMAPbI3, the 2D materials have larger band gaps and lower photoconductivity, whileBdAPbI4 based solar cells shows a comparable absorbed photon-to-current efficiency as compared toMAPbI3 based ones.